Surgical management of Basal cell carcinoma of the auricle with temporal bone extension – a case illustration - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Sa'at@Yusof, Azlin (2004)
Basal cell carcinoma frequently develop on the auricle. In advanced lesion, the tumor may extend into the ear canal with the invasion of the temporal bone. The involvement of the cartilage and bone makes radiation therapy less effective and surgery is the preferred treatment. In more difficult areas or with larger Basal Cell carcinoma, more complex surgery is required. Here we illustrate the surgical management of large Basal Cell Carcinoma of the auricle which involved the external ear canal and the temporal bone where wide local excision, auriculectomy and lateral temporal bone resection with sparing of the facial nerve was performed. The usage of trapezius skin island myocutaneus flap to reconstruct the surgical defect produced good aesthetic result.